2009
DOI: 10.1002/sia.3019
|View full text |Cite
|
Sign up to set email alerts
|

The interfacial feature of thermoplastic polystyrene composite filled with nitric acid oxidized carbon fiber

Abstract: The quality of interfacial interaction is dictated by the surface chemistry of the carbon fibers and the composition of the matrix. The composition of polystyrene was modified by the addition of maleic anhydride (MAH) grafted polystyrene. The surface properties of the various matrix formulations were characterized by contact angle. Carbon fibers were modified by oxidation in nitric acid. The surface composition of the carbon fibers was characterized. The interaction between modified polystyrene and the carbon … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 24 publications
1
4
0
Order By: Relevance
“…Table shows the results for PS-1, PA6-3, PA6-3/CB (100/20), and PA6-3/TiO 2 (100/20). τ app of the neat PS and PA6 is similar to the reported data, suggesting the validity of the present test.…”
Section: Resultssupporting
confidence: 88%
“…Table shows the results for PS-1, PA6-3, PA6-3/CB (100/20), and PA6-3/TiO 2 (100/20). τ app of the neat PS and PA6 is similar to the reported data, suggesting the validity of the present test.…”
Section: Resultssupporting
confidence: 88%
“…When considering the development of composites based on thermoplastic polymers, and more specifically PS, it is particularly difficult to ensure good interfacial adhesion between the matrix and the reinforcing agents. This shortage of compatibility between many reinforcing agents and PS is due to its inert nature and the lack of reactive groups (as compared with thermosetting systems and, indeed, other engineering thermoplastics), which limits the level of interaction . Hybrid materials with superior structural and functional properties can be obtained by incorporating nanofillers into polymer matrices.…”
Section: Introductionmentioning
confidence: 99%
“…This result indicates that the treatment of the recycled carbon fibre with nitric acid increased the fibres' surface reactivity by introducing functional groups containing oxygen. Similarly, previous research reported that treating carbon fibre with HNO3 produced the appropriate surface groups required to increase the IFSS of composites with polystyrene, allowing for an effective transfer of the stress from the matrix to the fibre [38]. Hydroxyl (OH) groups can form a chemical bond with the maleic anhydride groups on MAPE, while the main PE constituent of MAPE entangles with the polymeric matrix, improving the interfacial bond between the fibre and the matrix [31,32,34].…”
Section: Tensile Testing Of Compositesmentioning
confidence: 92%